Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

Please give solution of the following :-

Asked by 22nd July 2012, 12:07 PM
Answered by Expert
Answer:
Answer :  (i)  Given : f(x)= -2x + 5
To find  : The value of 2f(x)+f(-x)
 
Now ,
 f(x)= -2x + 5..................(1)

Replacing x by -x , we get ,
 f(-x)= 2x + 5 .................(2)
 
Now as asked by the question 
= 2 f(x) - f(-x) 
= 2 ( -2x + 5) - (2x+5)        {using (1) and (2) }
= -4x + 10 - 2x -5
= - 6x  + 5 Answer 
 
Note : Please ask one question at a time
Answered by Expert 22nd July 2012, 8:48 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp